Unity over diversity?: Teachers’ perceptions and practices of multicultural education in Kenya - Kuppens, Line; Ibrahim, Sulley; Langer, Arnim (Compare, 2020)
The current paper analyses how multicultural education is perceived and practised by secondary school teachers in Kenya, an ethnically diverse African country with a history of inter-ethnic tensions. The authors have conducted a large-scale survey among 925 secondary school teachers in Nairobi, complemented by 68 in-depth follow-up interviews. They analyse five dimensions of multicultural education using quantitative and qualitative methods . Their approach and focus are empirically and methodologically innovative since most studies in the field of multicultural education remain qualitative in nature, analyse attitudes of pre-service teachers, and are predominantly conducted in the United States. While Kenyan teachers value multicultural education and to a lesser extent implement multicultural teaching strategies, their findings indicate that Kenyan teachers seem to attach more importance to promoting unity than to recognising and celebrating diversity at school.